Pengaruh Work Life Balance Terhadap Kinerja Karyawan pada Lembaga Filantropy Cinta Qur’an Center - Syafaat Nuryadi; Maswanto (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to determine how much influence the Work Life Balance has on improving the performance Cinta Quran Center staff, the method used in this study is a quantitative research method with simple linear regression analysis as a data analysis technique, with 46 respondents consisting of 46 using a survey through a questionnaire to 46 employees of Cinta Quran Center, the results of this study can show that Work Life Balance has a positive and significant impact on employee performance. The total effect is 61.6%, the remaining 38.4% is influenced by variables not examined in this study.